KONSELING INDIVIDU (COGNITIVE BEHAVIOR THERAPY) UNTUK MENGURANGI KECANDUAN GAME ONLINE MOBILE LEGEND - sulistianingsih, sulistianingsih; Permana, Hara (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2022)
This study is intended to describe descriptively the implementation of individual counseling services through the Cognitive Behavior Therapy approach in reducing addiction to mobile legend games at SMP Negeri 12 Cirebon City. This research method is qualitative with case study type. The data were collected using participant observation techniques, personal interviews, and documentation from students' personal notes, the value of learning outcomes for one semester and individual counseling reports, where after the data was obtained, it was analyzed by means of data reduction analysis, data presentation, and drawing conclusions. Based on the results of this study, that a subject named Ando experienced dependence or addiction to online games due to communication factors with parents, social interaction with friends and curiosity about mobile legends. Meanwhile, Ilham is more addicted to mobile legends than Ando, which is 15-18 hours per day. The service provided by the BK teacher is individual counseling through a CBT approach that is centered on improving the subject's mindset which is expected to be more useful and positive in all of its activities.